Lactoferrin expression in breast cancer in relation to biologic properties of tumors and clinical features of disease - Naleskina, L.A.; Lukianova, N.Yu.; Sobchenko, S.O.; Storchai, D.M.; Chekhun, V.F. (Experimental Oncology, 2016)
Aim: To determine the patterns of lactoferrin (LF) expression in breast cancer (BC) in relation to biologic properties of the neoplasms and clinical features of the disease course. Materials and Methods: Clinical specimens of 266 BC patients (115 patients with BC of stages I–II — retrospective study, and 151 BC patients — prospective study) were analyzed. Morphological, immunohistochemical and statistical methods were used. Results: The number of LF-positive tumors in retrospective and prospective groups was similar (52.1 and 52.8%, respectively). Among common clinical criteria for prognosis of the disease outcome in BC patients (patient’s age; stage of the disease; histological type, differentiation grade, receptor status; presence of metastases), a strong correlation was found only between expression indexes of LF and estrogen receptors (ER). In ER-positive tumors expression of LF was significantly higher than in ER-negative tumors (35 vs 18%). 5-Year survival rate of BC patients was higher in LF-positive group (70 vs 52% in LF-negative group). The presence of regional metastasis tended to correlate with an increased number of LF-positive tumors. In the patients with invasive ductal carcinoma, expression level of LF moderately correlated with occurrence of luminal A subtype (r = 0.43), while in the patients with invasive lobular carcinoma this index strongly correlated with occurrence of luminal B subtype (r = 0.71). LF expression correlated positively with low and moderate differentiation grade of luminal B or basal tumors, and negatively with luminal B or basal tumors of high differentiation grade (r = −0.57 and −0.63, respectively). Conclusion: It has been shown that LF expression in breast tumors correlated with life expectancy of BC patients and important physiologic and clinical features of the disease, while the character of such relation strongly depended on molecular phenotype of tumor, i.e. luminal A, luminal B or basal.